Illustrated Book Design As A Medium For Introducing Toraja Carvings: Illustrated Book about Toraja Carvings - Rezki Amnur, Abdul Haq Rezki Amnur; Aswar; Satriadi (PT Ininnawa Paramacitra Edukasi, 2025)
The design of an illustrated book about Toraja carvings has become a necessary effort to preserve and introduce the cultural heritage of the Toraja Regency. Toraja is one of the regions in Indonesia that possesses an extraordinary wealth of culture, one of which is the traditional wood carving art known as Pa’sura’, which is rich in philosophical and aesthetic values. This design project employs the Research and Development (R&D) method with the 4D development model approach: Define, Design, Develop, Disseminate. In the Define stage, it involves identifying needs, analyzing data/information, and setting development objectives for the design. The Design stage includes visual planning, layout design, and the creation of visual concepts that depict the culture and traditions of the Toraja people. The Development stage focuses on creating a prototype of the illustrated book and validating it through feedback from cultural and design experts. In the final stage, Disseminate, the book is distributed through both print and digital platforms to reach a wider target audience. The outcome of this project is expected to produce an illustrated book that provides readers with a deep understanding of Toraja carving art and enhances appreciation for local cultural arts. This book is intended not only as an educational medium but also as a means of promoting Toraja culture at the national level.